Satisfaction in Old Age: Activity or Disengagement? - Sumi Rani Saha; Ashik Zaman (Journal of Sociological Research, 2024)
The aging process of human being is intertwined with two vital aspects of life experiences; work and retirement when elderly people face greater uncertainties than other age groups as they have to replace themselves in the newer environs with shifting roles. Thus, in this process, researchers have queries whether elderly disengage or withdraw, whether their disengagement or activity brings satisfactions and how is their attitude towards the functionality of disengagement. To measure these, disengagement and activity theories have been used with descriptive research design when respondents were selected purposively and interviewed Face-to-Face. Most of the elderly in Bangladesh believe themselves to be forced to retire. A significant portion of retired elderly answered that they wanted to be engaged instead retire but, in reality, most of them enjoy disengagement escaping from earlier activities that ensures their quality of life and satisfaction. After all, it is found that disengagement is functional as the sense that the elderly people give up their positions to the young as they are not able to defeat them in the activity level.